Shaking and Hand-Kissing Culture for Internalizing Respect Toward Teachers in Islamic Boarding Schools - Ari Susanto; Bagus Jamroji (PT. Caesarindo Triloka Persada, 2026)
This study examines the internalization of respect for teachers through the culture of shaking and hand-kissing within an Islamic Religious Education perspective at Darul Muslimin Muhammadiyah Islamic Boarding School. Using a qualitative case study approach, data were gathered from kiai, teachers, and students through interviews, observation, and documentation. The findings reveal that this cultural practice is not merely a tradition, but an effective medium for embedding values of respect, rooted in both religious teachings and educational norms. It significantly contributes to the development of students’ character, fostering humility, politeness, discipline, and stronger learning motivation. The internalization process is reinforced through exemplary behavior, habitual practice, and continuous social interaction within the boarding school environment. This study highlights that the culture of shaking and hand-kissing functions as a powerful hidden curriculum, playing a strategic role in strengthening Islamic character education in a holistic and sustainable manner.